Association of parental social support and dental caries in hispanic children - Lally, Casey; Maliq, Nihmath Nasiha; Schreiber, Madysen; Wilson, Anne; Tiwari, Tamanna (Frontiers in Oral Health, 2023)
This study describes social support of Hispanic parents and the correlation with dental caries in their children. A cross-sectional study design was utilized to assess the 157 parent-child triads recruited from the Children's Hospital Colorado Dental Clinic. The Basic Research Factors Questionnaire (BRFQ) survey was utilized to assess parents' oral health knowledge, attitudes, behavior, and other psychosocial measures with social support as the main predictor variable. Bivariate associations between the independent variables and dmfs were conducted. Independent variables with a bivariate association of p<0.2 for the outcome variable were included in the multivariable linear regression model. Dental caries in children was significantly associated with less overall parental social support (β = -10.10, p = 0.03). Overall social support was divided into four sub-categories: errand help, money help, childcare help, and transportation help. Dental caries decreased by 7.70 units for every 1-unit increase in transportation help (β = -7.70, p = 0.03). A significant association was observed between parental knowledge on dental utilization and dmfs (β = -2.70, p = 0.04). In the multivariable linear regression model, caries was significantly associated with social support (β = -11.18, p = 0.02) and knowledge on dental utilization (β = -3.84, p = 0.01). The study concludes that a higher level of social support and knowledge on dental utilization for Hispanic parents is correlated with lower rates of dental caries in their children.